The Košice meteorite fall: Recovery and strewn field. (20th April 2015) - Tóth, Juraj; Svoreň, Ján; Borovička, Jiří; Spurný, Pavel; Igaz, Antal; Kornoš, Leonard; Vereš, Peter; Husárik, Marek; Koza, Július; Kučera, Aleš; Zigo, Pavel; Gajdoš, Štefan; et al.
Abstract We provide the circumstances and details of the fireball observation, search expeditions, recovery, strewn field, and physical characteristics of the Košice meteorite that fell in Slovakia on February 28, 2010. The meteorite was only the 15th case of an observed bolide with a recovered mass and subsequent orbit determination. Despite multiple eyewitness reports of the bolide, only three videos from security cameras in Hungary were used for the strewn field determination and orbit computation. Multiple expeditions of professionals and individual searchers found 218 fragments with total weight of 11.3 kg. The strewn field with the size of 5 × 3 km is characterized with respect to the space distribution of the fragments, their mass and size‐frequency distribution. This work describes a catalog of 78 fragments, mass, size, volume, fusion crust, names of discoverers, geographic location, and time of discovery, which represents the most complex study of a fresh meteorite fall. From the analytical results, we classified the Košice meteorite as an ordinary H5 chondrite.